Evaluation of an Ophthalmology Session for Third-Year Medical Students at the University of Colorado School of Medicine - Kelley, Judas Z.; Singh, Jasleen K. (Journal of Academic Ophthalmology, 2018)
Background Medical school ophthalmology education continues to be marginalized, creating the challenge of teaching students how to adequately diagnose and manage common ocular diseases in a limited time.Objective This study aimed to improve the ophthalmic medical knowledge and clinical skills of third-year medical students.Methods This curriculum was provided to 76 out of 124 third-year medical students in the 2016 class at the University of Colorado-Denver School of Medicine program. It was a half-day session that incorporated lectures, problem-based cases, and clinical skills. Participating students were given a self-reflection survey on their knowledge at the beginning and end of the session. Participating students were given a pre-test and post-test 6 months later via SurveyMonkey. Another quiz was given to all students within the class. Comparisons of pre- and post-tests, pre- and post-surveys, and quiz results in the participating and nonparticipating groups were made.Results Participating students' mean pre-test score was 61.8% (n = 76) and post-test score was 72.3% (n = 47), p < 0.01, indicating a significant increase in knowledge. There was an increase in 2 points on the Likert scale of understanding in ophthalmology between surveys. Participating students received a quiz mean score of 61.2%, which was significantly higher than those in the nonparticipating group (54.3%), p < 0.05.Conclusion This session improved medical students' confidence and medical knowledge in ophthalmology.
Keywords: medical student education; program evaluation; new curriculum